2022
DOI: 10.3389/fendo.2022.886957
|View full text |Cite
|
Sign up to set email alerts
|

Reduced leukocyte mitochondrial copy number in metabolic syndrome and metabolically healthy obesity

Abstract: ObjectiveThis study aimed to investigate the associations between peripheral blood leukocyte mitochondrial copy number, metabolic syndrome, and adiposity-related body composition phenotypes in a high prevalence population.MethodsA single center cross-sectional study was conducted, consisting of 521 middle-aged subjects of Maltese-Caucasian ethnicity. Participants were stratified according to the presence of metabolic syndrome and different metabolic health definitions based on NCEP-ATP III criteria. Relative l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 94 publications
0
8
0
Order By: Relevance
“…Meta-analyses have reported that lower mtDNAcn in peripheral blood was associated with higher BMI, visceral fat area, and waist circumference [17] and increased odds of obesity, hyperlipidemia, and other metabolic syndrome components [9,36]. mtDNAcn in peripheral blood leukocytes was also negatively associated with BMI, waist circumference, and triglyceride levels in nurses and a population of Maltese-Caucasian participants [18,37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meta-analyses have reported that lower mtDNAcn in peripheral blood was associated with higher BMI, visceral fat area, and waist circumference [17] and increased odds of obesity, hyperlipidemia, and other metabolic syndrome components [9,36]. mtDNAcn in peripheral blood leukocytes was also negatively associated with BMI, waist circumference, and triglyceride levels in nurses and a population of Maltese-Caucasian participants [18,37].…”
Section: Discussionmentioning
confidence: 99%
“…In adult populations, peripheral blood mtDNAcn is negatively associated with adiposity markers such as BMI, waist circumference, and visceral fat area [17,18]. However, there has been little research investigating the relationship between mitochondrial content and adiposity in children [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The connection between mtDNAq and obesity has been established 10,34,35 , yet the exploration of causal pathways has been limited. We identified a dualistic relationship between mtDNAq and obesity-related outcomes which pointed to either causation from mtDNAq to several obesity-related outcomes or the presence of unmeasured within-individual confounding.…”
Section: Discussionmentioning
confidence: 99%
“…A relationship between mitochondrial-mediated oxidative stress-defense mechanisms and weight change has been suggested in a population-based study, by demonstrating that the leukocyte mtDNA copy number is inversely associated with weight, BMI, waist circumference, and waist–hip ratio [ 16 ]. Furthermore, the association between the reduced leukocyte mtDNA copy number, obesity, and metabolic syndrome was widely described in the literature, expanding the spectrum of associations between the mtDNA copy number and metabolic phenotypes in different populations [ 41 ]. Telomere lengths and the mtDNA copy number may be additional markers of the dynamic metabolic homeostasis in patients with obesity.…”
Section: Discussionmentioning
confidence: 99%